Experimental modelling of the effects of CXA bombardment on image quality of the first mirrors in ITER - Konovalov, V.G.; Shapoval, A.N.; Volkova, O.Yu.; Voitsenya, V.S. (Вопросы атомной науки и техники, 2005)
In optical methods of plasma diagnostics in large fusion devices (FD) the use of first mirrors (FM) is supposed. To make the right choice of FM material the modeling studies are needed of the degradation rates of reflectance and image transmission quality (ITQ) under sputtering in FDs. In the present paper the method is suggested and applied for evaluation of ITQ. The use of scheme with photoelectrical registration of the luminous object image allows measuring the dynamics of the change of the contrast and resolving power of mirror depending on the depth of layer eroded due to bombardment with deuterium ions. As an example, the comparative results are presented on degradation of optical properties of two Cu mirror samples with coarse-and small-grain structures.